Three Dangerous Loops Of Lipoproteine-Associated Phospholipase A2 Activity On Increasing LDL Aterogenecity - Retno Susilowati; Djanggan Sargowo; Askandar Tjokroprawiro (The Indonesian Heart Association, 2019)
Background. Hypercholesterolemia is a major classic risk factor for cardiovascular disease, but there are 35%-40% cases of cardiovascular patients have a normal cholesterol levels. Lp-PLA2 is an enzyme that produced and secreted by macrophages as a response to the lipid peroxide formation, especially the platelet activating factor compound and phosphocholine peroxide. Lp-PLA2 is correlated with classic risk factor of cardiovascular disease, although that correlation with number of foam cell at early stage of atherosclerosis is not clear yet. This study aims to determine whether Lp-PLA2 levels correlated with classic risk factors of atherosclerosis and the number of foam cell, and the role of Lp-PLA2 enzyme in foam cells formation.Methods. This study observes the change of Lp-PLA2, F2-Isp, MDA, TC, LDL, HDL levels in rat serum at 3 levels of early atherogenesis, Ath-I, Ath-II and Ath-III were made on the number of foam cells. The number of cells was observed on all aortic cross sectional surfaces, using the Oil-Red-O staining. The LDL-C content was measure using the Fiedwall formula, MDA content was measure by using TBA-test, the observe of F2-isoprostane and Lp-PLA2 followed the procedure Elisa methods. Results. Anova test results among the 3 initial atherosclerotic levels showed a very significant difference (p<0.01) on Lp-PLA2 plasma content. The LSD test results represented an increase in Lp-PLA2 enzyme levels significantly since AthII stage. Path analysis refers that correlation value between the Lp-PLA2and the number of foam cell (r=0.48) were higher than that of the LDL (r=0.42), was neither correlated with MDA nor F2-Isp, the highest correlation occurred between Lp-PLA2 and LDL compared to the others parameters (r = 0.58). Path analysis also showed no correlation between cell numbers with MDA and F2-Isp, but LDL levels are correlated significantly with of oxidative stress markers MDA levels (r = 0.32) and correlated very significantly with F2-Isp (r = 0.69).Conclussion. It can be concluded that elevated levels of Lp-PLA2 increase atherogenecity of LDL, due to increased inflammation, stress oxidation and elevated levels of Lp-PLA2 itself, wich are interconnected with proatherogenic loops.